Macam Urgensi Amtsal Dalam Al-Quran - Makrifah, Nurul (STAI Nurul Huda Kapongan Situbondo, 2020)
Al-Quran is a divine word that has a lot of beauty in it, both meaning and language. One of the beauty of the language is in terms of metaphorical content or called amtsal. Amtsal is like an expression of something that matches other expressions because of similarities. For this reason, the researcher aims to describe the types of Amtsal in the Quran, as well as the urgency of Amtsal in the Quran. Through descriptive methods and library research, it can be seen that there are several types in amtsal including al-amtsal al-musharahah, al-amtsal al-kaminah, and amtsal mursalah. While the urgency of amtsal in the quran includes the matsal drawing the image of the mumatsalah, amtsal serves as an invitation to be logical, an impulse to always do good, give encouragement and an attitude of love to do good, used to praise or to denounce something, then amtsal used to sharpen the power of human reasoning.